Modeling of bud break of Scots pine in northern Finland in 1908–2014 - Salminen, Hannu; Jalkanen, Risto (Frontiers in Plant Science, 2015)
Bud break and height-growth of Scots pine (Pinus sylvestris L.) in the northern boreal zone in Lapland, Finland, was followed through the entire growing seasons in 2001–2003 and 2008–2010 in sapling stands representing two different locations in northern Finland about 250 kilometers apart along latitudinal transect. The field measurements continued at the southern site also through 2011–2013. Air temperature was recorded hourly at the sites. A simple optimization algorithm (GA) was used to adjust parameters of the models predicting the timing of bud break of Scots pine in order to minimize the difference between observed and predicted dates. The models giving the best performance and century-long daily temperatures were used to reconstruct bud-break time series. The temperature observations were recorded during 1908–2014 in Sodankylä that locates in-between the sapling stands in north–south direction and during 1877–2014 in Karasjok that is in Norway about 145 kilometers north-west from the northernmost stand of this study. On average buds began to extend on the beginning of May in the southernmost stand and in mid-May in the northernmost stands, and the variation between years was in the range of three weeks. Simple day-length-triggered (fixed date) model predicted most accurately the date of bud break; RMSE was 2 and 4 days in the northern and southern site, respectively. The reconstructed bud-break series indicate that based on temperature observations from Sodankylä, growth onset of Scots pine clearly has advanced since 1960s but was as currently early in the 1920s and 1950s. Temperature record from Karasjok indicated similar variation but there was a weak linear trend advancing bud break by about 3–4 days during a 100 years period.